Stability criterion and its calculation for sail-assisted ship - Yihuai Hu (International Journal of Naval Architecture and Ocean Engineering, 2015)
Stability criterion and its calculation are the crucial issue in the application of sail-assisted ship. How- ever, there is at present no specific criterion and computational methods for the stability of sail-assisted ship. Based on the stability requirements for seagoing ships, the stability criterion of the sail-assisted ships is suggested in this paper. Furthermore, how to calculate the parameters and determine some specific coefficients for the ship stability calculation, as well as how to redraw stability curve are also discussed in this paper. Finally, to give an illustration, the proposed method is applied on a sail assisted-ship model with comments and recommendations for improvement.